Clinical researchImpact of obesity and adipokines on cardiac structure and function in men with first myocardial infarction - Piestrzeniewicz, Katarzyna; Łuczak, Katarzyna; Maciejewski, Marek; Goch, Jan Henryk (Archives of Medical Science, 2008)
Introduction: Alterations in cardiovascular function have been observed in obese patients. The aim of the study was to evaluate the impact of obesity and plasma concentration of the adipokines: leptin, adiponectin and resistin on cardiac structure and function. Material and methods: Out of patients with first acute myocardial infarction (AMI) 40 obese males aged up to 65 years formed group I and 40 lean males group II. Anthropometric measurements, echocardiographic parameters and plasma adipokines concentrations were analyzed. Results: The anthropometric measurements, leptin and resistin were significantly higher, whereas adiponectin was lower in group I. Most morphological and diastolic function parameters significantly differed between groups. Myocardial performance index was higher in obese patients and correlated with leptin and resistin. Left ventricular hypertrophy (LVH) was observed in 24 patients in group I and 10 patients in group II (60 vs. 25%, P<0.01). In univariate regression analysis LVH was related to obesity, hypertension and adipokines but only hypertension and leptin independently increased the probability of LVH. No relation between impaired systolic function (EF<55%) and the analyzed parameters was found. Abnormal left ventricular relaxation was present in 8 patients in group I and 3 patients in group II (20 vs. 7.5%, NS). A relation between abnormal relaxation and hypertension, diabetes and adipokines was revealed, the independent variables being hypertension and leptin. Conclusions: Obesity is associated with alterations in cardiac structure, diastolic function and LVH. Leptin is related to LVH and abnormal left ventricular relaxation.